1998
DOI: 10.1007/s001340050677
|View full text |Cite
|
Sign up to set email alerts
|

Enteral nutrition in intensive care patients: a practical approach

Abstract: Severe protein-calorie malnutrition is a major problem in many intensive care (ICU) patients, due to the increased catabolic state often associated with acute severe illness and the frequent presence of prior chronic wasting conditions. Nutritional support is thus an important part of the management of these patients. Over the years, enteral nutrition (EN) has gained considerable popularity, due to its favorable effects on the digestive tract and its lower cost and rate of complications compared to parenteral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
106
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(114 citation statements)
references
References 68 publications
2
106
0
6
Order By: Relevance
“…Diarrhoea is a common complication of EN in the ICU (35,36) . Although it is rarely considered a life-threatening complication, diarrhoea may increase the risk of dehydration and incontinence, and thus increase the risk of wound infection as well as being burdensome to patients and nursing staff (37 -39) .…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhoea is a common complication of EN in the ICU (35,36) . Although it is rarely considered a life-threatening complication, diarrhoea may increase the risk of dehydration and incontinence, and thus increase the risk of wound infection as well as being burdensome to patients and nursing staff (37 -39) .…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional guidelines were followed in the Leuven studies [2,11,34]. Enteral feeding was attempted as soon as possible when the patients were haemodynamically stable, but when the energy intake target could not be reached, parenteral feeding was given early to compensate for the deficit.…”
mentioning
confidence: 99%
“…In another study, McClave 11 et al evaluated the supply of enteral nutrition only in ICU patients and found that they received an average of 52% of TEE, and that adequacy was approximately 78% in relation to the prescribed volume, significantly lower than the one found in the present study. Thus, according to the literature, the caloric intake offered to hospitalized patients in general is insufficient, which may be compromising the individuals' nutritional status and affecting and/or aggravating their prognosis [9][10][11]23 .…”
Section: Discussionmentioning
confidence: 99%
“…The type of diet or enteral product offered should be chosen based on the individual characteristics of each patient, and according to the needs generated by the pathologies from which they are affected 9,10 . Patients who are at risk of malnutrition are potential candidates for enteral nutritional therapy, since it allows for a more effective control of the patient's nutrition.…”
mentioning
confidence: 99%
See 1 more Smart Citation